2022
DOI: 10.3389/fgene.2022.927142
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of ferroptosis-related lncRNA signatures as a novel prognostic model for glioma

Abstract: Background: Ferroptosis is a newly discovered form of regulated cell death with distinct properties and recognizing functions involved in physical conditions or various diseases, including cancers. However, the relationship between gliomas and ferroptosis-related lncRNAs (FRLs) remains unclear.Methods: We collected a total of 1850 samples from The Cancer Genome Atlas (TCGA) and Genotype Tissue Expression (GTEX) databases, including 698 tumor and 1,152 normal samples. A list of ferroptosis-related genes was dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%